Are All Oral COX-2 Selective Inhibitors the Same? A Consideration of Celecoxib, Etoricoxib, and Diclofenac. (9th December 2018) - Walker, Chris
Abstract : Nonsteroidal anti-inflammatory drugs (NSAIDs) have been widely used for the treatment of arthritic conditions. Drugs in this heterogeneous class alleviate pain and inflammation by inhibiting cyclooxygenase-2 (COX-2). Cyclooxygenase-1 (COX-1) inhibition has traditionally been associated with increased gastrointestinal (GI) harm, whereas increased COX-2 selectivity has more recently become associated with greater risk of cardiovascular (CV) harm. When the entirety of data is considered, NSAIDs can be seen to exhibit a range of COX isoform selectivity, with all oral NSAIDs appearing to be associated with an increase in CV events. This review focuses on a comparison of the efficacy and the GI and CV safety profiles of three commonly used NSAIDs—celecoxib, etoricoxib, and diclofenac—using direct comparisons where available. While all three treatments are shown to have comparable efficacy, there are differences in their safety profiles. Both celecoxib and etoricoxib are associated with less GI harm than diclofenac despite the similarity of its COX-2 selectivity to celecoxib. Each of the three medicines under consideration is associated with a similar overall risk of CV events (fatal and nonfatal heart attacks and strokes). However, there are consistent differences in effects on blood pressure (BP), reported both from trials using ambulatory techniques and from meta-analyses of randomized trials, reporting investigator determined effects, with etoricoxib being associated with a greater propensity to destabilize BP control than either diclofenac or celecoxib.